2020
DOI: 10.1126/sciadv.aaz3910
|View full text |Cite
|
Sign up to set email alerts
|

Four-wave mixing of topological edge plasmons in graphene metasurfaces

Abstract: We study topologically-protected four-wave mixing (FWM) interactions in a plasmonic metasurface consisting of a periodic array of nanoholes in a graphene sheet, which exhibits a wide topological bandgap at terahertz frequencies upon the breaking of time-reversal symmetry by a static magnetic field. We demonstrate that due to the significant nonlinearity enhancement and large lifetime of graphene plasmons in specific configurations, a net gain of FWM interaction of plasmonic edge states within the topological b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…Moreover, graphene plasmons, the energy carriers in graphene based photonic systems, exhibit a tight optical field confinement and have long intrinsic relaxation times in the terahertz and up to mid-infrared frequency range [18]- [22]. Indeed, it has been shown that a periodically patterned graphene nanostructure under a static magnetic field can host topological one-way edge plasmons up to infrared frequencies [23]- [25], owing to the breaking of the time reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, graphene plasmons, the energy carriers in graphene based photonic systems, exhibit a tight optical field confinement and have long intrinsic relaxation times in the terahertz and up to mid-infrared frequency range [18]- [22]. Indeed, it has been shown that a periodically patterned graphene nanostructure under a static magnetic field can host topological one-way edge plasmons up to infrared frequencies [23]- [25], owing to the breaking of the time reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been demonstrated that the strength of third-order nonlinear optical interactions in graphene is several orders of magnitude larger than in typical semiconductors [33][34][35][36]. More importantly, these nonlinear optical interactions can be further enhanced upon resonant excitation of SPPs in graphene structures, which leads to a number of exciting applications [18][19][20][37][38][39][40][41][42][43][44][45][46], including frequency mixing [18], photodetectors [25], generation of spatial solitons [43,44], physical systems with tunable Dirac points [45], and Anderson light localization at the nanoscale [46].…”
mentioning
confidence: 99%
“…These figures show the electric field calculated along the edge of the finite graphene plasmonic system, at a distance of 80 nm above the surface of the graphene metasurface. These results demonstrate that a net gain can be achieved when γ≤0.2 THz [6]. The main reason why this important phenomenon occurs is that the energy of the pump wave could be effectively transferred to the signal at a rate larger than the rate at which the signal power dissipates.…”
Section: Four-wave-mixing Interaction Of One-way Graphene Plasmon Modesmentioning
confidence: 75%